Penggunaan Metode Balanced Scorecard dan SWOT sebagai alat Pengukuran Kinerja Perusahaan Pada CV. Aqsha Kota Probolinggo - Elis Susan Dwi; R. Hery Koeshardjono; Judi Suharsono (Fakultas Ekonomi Universitas Panca Marga, 2020)
The purpose of this study was to analyze the measurement of company performance using the Balanced Scorecard and SWOT methods on CV. Aqsha Probolinggo. Researchers used descriptive analysis with a quantitative approach, the method of collecting data using questionnaires and sampling techniques using Nonprobability sampling convenience sampling. he analytical tool used in this study is that the SWOT method is used to bring up alternative strategies of internal and external factors of the company, then translated into strategic goals into the perspective of the Balanced Scorecard to develop a strategy map, determine and calculate measures / targets, set targets strategic initiatives to improve company performance.The results of the study resulted in 11 strategic alternatives which were translated into 11 strategic objectives. Among them in the financial perspective there is a measure of ROI with a value of 0.30%, profit margin with a value of 0.31%, total assets turn over with a value of 9 times, on customer perceptions produces a number of customer retention with a value of 60%, in the perspective of internal business processes focuses on the delivery of existing efficient, consistent and timely completion of the product, while the learning and growth perspective shows that employee satisfaction is at an interval of 316 so employee satisfaction can be categorized as satisfied. Keywords: Performance, Balanced Scorecard dan SWOT.